Radiographic assessment of symptomatic knee osteoarthritis in the community: definitions and normal joint space. Issue 10 (1st October 1998) - Lanyon, Peter; O'Reilly, Sheila; Jones, Adrian; Doherty, Michael
Abstract : OBJECTIVE: To evaluate radiographic features of osteoarthritis (OA) to determine which is more closely associated with knee pain and hence might be used as a radiographic definition of OA in the community. To evaluate joint space width in normal subjects. METHODS: 452 subjects from a case-control community study of knee pain (294 women, 158 men, mean age 62 years, range 40–80) underwent AP standing and mid-flexion skyline radiographs. Joint space width, measured by metered calliper to 0.1 mm, and graded individual features of OA (osteophyte 0–3, narrowing 0–3, sclerosis 0–1, cysts 0–1) were assessed in all three compartments independently by two observers who were blind to clinical status. Subjects were categorised as having knee pain by a positive response to both parts of the question "Have you ever had pain in or around the knee on most days for at least a month? If so, have you experienced any pain during the last year?" RESULTS: Intraobserver reproducibility for joint space width measurements was to within ±0.4 mm (95% CI for limits of agreement); κ values for grading were >0.7. One hundred and twenty five subjects were without knee pain or osteophyte. In these radiographically normal knees, mean joint space width varied according to sex but did not decrease with age. A definition based on the presence of osteophyte ⩾grade 1 in any compartment was more efficient at predicting pain than definitions based on either measurement or grading of joint space; there was no clear threshold of joint space loss at which the likelihood of pain substantially increased. The presence of osteophyte at the patellofemoral joint (PFJ) was more sensitive but less specific than at the tibiofemoral joint (TFJ); the addition of PFJ assessment improved sensitivity from 38.1% to 62.3% with a reduction in specificity from 82.7% to 58.7% for the presence of knee pain. CONCLUSION: Among men and women in the community, osteophyte is the radiographic feature that associates best with knee pain. Radiographic assessment of both TFJ and PFJ should be included in all community studies. Joint space loss is not a feature of asymptomatic aging, and there is not a biological cut off for joint space width below which the likelihood of knee pain markedly increases.